Unemployment and Health: Experiences Narrated by Young Finnish Men. (January 2015) - Björklund, Ove; Söderlund, Maud; Nyström, Lisbet; Häggström, Elisabeth
Studies have shown that the experiences and consequences of unemployment can affect people differently depending on, for example, age and gender. The purpose of the present study was to describe young Finnish men's experiences of being unemployed as well as how their experiences of health emerged. Fifteen young unemployed Finnish men in the age range 18 to 27 years were interviewed face to face. Purposive sampling was used to increase the variation among informants. The interview texts were analyzed using both manifest and latent qualitative content analysis. The present results showed that the young men were strongly negatively affected by being unemployed. They described how they had slowly lost their foothold. They also described feelings of shame and guilt as well as a flight from reality. The present results show that even young men who have only experienced shorter periods of unemployment, in this study periods between 2 and 6 months, are negatively affected, for example, with regard to their identity and emotional life. Further research is needed to describe and elucidate in more detail the effects of unemployment on men of different ages and living in different contexts.